Parenting and Australian trans and gender diverse people: An exploratory survey. Issue 2 (2nd April 2016) - Riggs, Damien W.; Power, Jennifer; von Doussa, Henry
ABSTRACT: Growing numbers of Australian trans and gender diverse people desire to become parents, yet many who do so experience a lack of support and recognition. This article reports on an online survey completed by 160 trans or gender diverse people. The survey included general demographic questions, in addition to questions related to (1) current parenting arrangements, (2) modes of family formation, (3) the desire to have children in the future, and (4) support or discrimination from families of origin. In regard to the findings, only a minority of participants (39) were already parents; however 21 participants indicated that they desired to have children in the future. Participants who were already parents were older than those who were not, and conversely, participants who desired to have children in the future were younger than those who did not. Discrimination from family of origin was negatively correlated with support for parenting, while support from family of origin was positively correlated with desire to have children. The paper concludes by suggesting that support from service providers is important for this potentially vulnerable group who may not experience support from their families of origin and who may perceive themselves as having limited pathways to parenthood.